An investigation into the antecedents influencing unethical consumer behavior / Nazahah Abd Rahim, Muna Abdul Jalil and Shakirah Mohd Saad - Abd Rahim, Nazahah; Abdul Jalil, Muna; Mohd Saad, Shakirah (Research Management Institute (RMI), 2012)
The issue of consumer ethics is always going to be a neverending story as such attributes is embedded unconsciously and naturally in our daily lives. Although rationally behaving unethically is generally unacceptable, consumers are less likely to notice and to be aware of their own ethical behaviors. Unethical behaviors such as shoplifting, deshopping, counterfeiting, getting too much change and not saying anything, cutting queues and misrepresent child's age to get discounts are sometimes perceived as something normal, a norm or a habit. Consumers tend to just be ignorant. Consumer ethics is defined by Muncy and Vitell (1992) as "the moral principles and standards that guide behavior of individuals or groups as they obtain and dispose of goods and services". Consumer ethics are important to business not only due to the absolute cost of loss but also due to the increasing cost of security. The National Retail Security Survey conducted in USA finds that shoplifting, employee theft, vendor fraud and administration errors to cost an estimated US$32 billion in 2000 (Stores, 2002). Berstein (1985) posits consumers are "out-doing" big business and the government at unethical behavior…